2014
DOI: 10.2337/dc13-2238
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of a 3-Day Basal-Bolus Insulin Delivery Device in Individuals With Type 2 Diabetes

Abstract: OBJECTIVEThis study tested the feasibility of transition from multiple daily injections (MDI) to a 3-day, basal-bolus insulin delivery device (PaQ) for type 2 diabetes (T2D). RESEARCH DESIGN AND METHODSTwenty MDI-treated individuals with T2D with HbA 1c £9% (75 mmol/mol) were enrolled in a single-center, single-arm pilot study, lasting three 2-week periods: baseline (MDI), transition to PaQ, and PaQ therapy. Feasibility of use, glycemic control, safety, and patient satisfaction were assessed. RESULTSNineteen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…This increased satisfaction may have contributed to the participants taking more mealtime insulin administrations than at baseline, which could also have been a factor in better HbA 1c control. The observation of increased mealtime bolus administration with the PAQ was also seen in the first PAQ proof‐of‐concept study .…”
Section: Discussionmentioning
confidence: 58%
“…This increased satisfaction may have contributed to the participants taking more mealtime insulin administrations than at baseline, which could also have been a factor in better HbA 1c control. The observation of increased mealtime bolus administration with the PAQ was also seen in the first PAQ proof‐of‐concept study .…”
Section: Discussionmentioning
confidence: 58%
“…24 Prior studies have used CGM to evaluate glycemic measures with insulin pump therapy for T2D; however, these studies have not assessed the use of RHI. [25][26][27][28] Lane et al 29 used periodic 72-h CGM during their 1-year study of 20 patients with severe insulin-resistant T2D who were administered U500 insulin by CSII. They found that the percentage of time spent in the glycemic range improved significantly, and there was no increase in hypoglycemia, compared with prior MDI regimens.…”
Section: 011mentioning
confidence: 99%
“…A semi-disposable insulin device called PaQ (Cequr SA, Montreux, Switzerland) incorporates an electronic messenger with an infuser unit to alert patients when it is time to replace the device. PaQ, which has been approved in Europe, is designed to administer basal-bolus therapy and is intended to be worn for 3 days ( 21 ). The timeline for filing with the FDA to secure approval in the United States is not available.…”
Section: Practical Considerations and Perceptionsmentioning
confidence: 99%